Hardseededness in two Medicago species as affected by water stress during seed development - Patanè C.; Cosentino S.L.; Copani V. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
In order to evaluate the effect of water stress on hardseededness during seed development in two Medicago species native to a natural pasture in Sicily (south Italy), an experiment was carried out in a growth chamber, where plants were grown in pots and five different water treatments were applied (irrigation at 1, 4, 8, 12 or 16-day intervals). Water treatments were differentiated from the beginning of the fruit-set stage. Leaf transpiration was progressively reduced with the lengthening of the dry interval, from 1.81 to 0.45 ?g cm-2s-1 on average in M. rugosa, and from 2.34 to 0.95 ?g cm-2s-1 in M. orbicularis. Stress degree-day (difference between leaf temperature and chamber temperature) increased with the reduction of irrigation frequency. In the germination trials performed at the end of the growth chamber experiment, the lower germination percentage corresponded to seeds produced in plants irrigated at longer intervals, highlighting a water stress effect during seed filling, promoting hardseededness.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)